Ignition and break-down of the gas discharge in magnetic field - Zykov, A.V.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2015)
The characteristics of the low pressure discharge in crossed electric and magnetic fields in the cases of magnetically insulated diode and electron anode layer with free cathode boundary are described. The phenomenal theory of the gas discharge switch-on was developed. The theory is based on Townsend ionization approach, adapted to the gas discharge in magnetic field. Also the mechanism of discharge initiation based on combined ionization of gas by electron avalanches and high energy γ-electrons is considered. The theory was compared with experimental characteristics breakdown and ignition curves of Hall-type ion source “Radical”. Представлено характеристики розряду низького тиску в схрещених електричному і магнітному полях з вільною і фіксованою катодними межами. Розвинена феноменологічна теорія запалювання газового розряду на основі теорії Таунсенда, яка адаптована до розряду в магнітному полі. Також розглянуто механізми пробою розряду електронними лавинами і запалювання високоенергетичними γ-електронами. Проведено порівняння теорії з кривими пробою й запалювання розряду в джерелі іонів холлівського типу «Радикал». Представлены характеристики разряда низкого давления в скрещенных электрическом и магнитном полях со свободной и фиксированной катодными границами. Развита феноменологическая теория зажигания газового разряда на основе теории Таунсенда, адаптированной к разряду в магнитном поле. Также рассмотрены механизмы пробоя разряда электронными лавинами и зажигания высокоэнергетичными γ-электронами. Проведено сравнение теории с кривыми пробоя и зажигания разряда в источнике ионов холловского типа «Радикал».